2022
DOI: 10.7759/cureus.21500
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection in Pregnancy and Its Effects on Maternal and Perinatal Outcome: A Retrospective Study

Abstract: BackgroundA urinary tract infection (UTI) is a common medical condition complicating pregnancy with adverse maternal and perinatal outcomes. This study aimed to assess any adverse maternal and perinatal morbidity related to UTI in pregnancy, focusing on identifying common uropathogens and their antibiotic sensitivity and resistance patterns. MethodsWe conducted a retrospective cohort study at Corniche Hospital, Abu Dhabi. The study population consisted of 549 women in the exposed group (i.e., those with at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…GBS infection can lead to invasive diseases such as bacteremia and skin/soft tissue infection in nonpregnant adults, the burden of which has been increased significantly during the past few years [ 2 4 ]. The GBS carriage of pregnant women can be chronic, intermittent or transient and is implicated in urinary tract infection, premature rupture of membranes, and preterm birth [ 5 7 ]. According to a literature, the prevalence of GBS invasive diseases in pregnant women was twice as much as that in nonpregnant women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…GBS infection can lead to invasive diseases such as bacteremia and skin/soft tissue infection in nonpregnant adults, the burden of which has been increased significantly during the past few years [ 2 4 ]. The GBS carriage of pregnant women can be chronic, intermittent or transient and is implicated in urinary tract infection, premature rupture of membranes, and preterm birth [ 5 7 ]. According to a literature, the prevalence of GBS invasive diseases in pregnant women was twice as much as that in nonpregnant women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Balachandran et al showed women with UTI during pregnancy to be more likely to have preterm delivery (12) . According to a meta-analysis conducted by Palupi et al (2022), in pregnant women with UTI, the occurrence of preterm labor increased by 2.19 times as compared with those without (13) .…”
Section: Resultsmentioning
confidence: 99%
“…were the main determinants of infectious complications in our cohort of patients. This bacterial spectrum corresponds to the pathogenic microorganisms associated with UTI in pregnancy [ 27 , 28 , 29 ]. All patients underwent antibioprophilaxis with a third-generation cephalosporin, Ceftriaxone, which was continued for 14 days if an UTI was confirmed by urine culture.…”
Section: Discussionmentioning
confidence: 99%